ANALISIS PENGGUNAAN BANGKU SEKOLAH UKURAN FIXED DAN ADJUSTABLE UNTUK ANAK SEKOLAH DASAR - Sari, Ratih Ardia; Swara, Suluh Elman (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2014)
School bench is one of the facilities that identified could cause musculoskeletal pain in school-age children. During class, students often sit with poor posture, back and neck bent in a long time so that musculoskeletal pain often occur in a classroom. Based on research conducted by Ira Idawati, school bench design needs to be different for each level of class because children have different anthropometric at each grade level elementary school-age. This can be done by designing school bench with fixed or adjustable size. If school decides to use fixed size bench, it is recommended to use several size of bench based on the level of the class. But if school used with adjustable size, the school could only buy one type and size of bench with a certain level of ergonomics. This study analyzed the used of the fixed and adjustable school bench design in elementary school based on economically and ergonomics. The result from this study shown that elementary student who sit on fixed size bench had a larger risk to the body than adjustable bench size from REBA and RULA scores. This suggests that adjustable bench was recommended for teaching and learning process facilities for health and to prevent injury on child. From economic terms, the value of the Net Present Value for fixed size bench is more economical than the adjustable one. From this two aspect, the elementary school had references to make school bench type decision.